Malnutrition and obesity: influence in mortality and readmissions in chronic obstructive pulmonary disease patients. (9th May 2013) - Zapatero, A.; Barba, R.; Ruiz, J.; Losa, J. E.; Plaza, S.; Canora, J.; Marco, J.
Abstract: Background: The present study aimed to assess the association of obesity and malnutrition with the mortality of hospitalised patients with acute exacerbation of chronic obstructive pulmonary disease (COPD) and the risk of readmission in <30 days. Methods: A retrospective chart review of consecutive patients admitted with COPD as the primary reason for discharge in Spain between 1 January 2006 and 31 December 2007 was performed. Patients with a diagnosis of obesity or malnutrition in the hospital discharge clinical report were identified. The in‐hospital mortality and re‐admittance 30 days after discharge indices of obese and malnourished patients were compared against the subpopulation without these diagnoses. Results: Of the 313 233 COPD admittances analysed, there were 22 582 (7.2%) diagnoses of obesity and 6354 (2.0%) diagnoses of malnutrition. In‐hospital global mortality and the re‐admittance risk were 12.0% and 16.7%, respectively. Obese patients showed a lower in‐hospital mortality risk [odds ratio (OR) = 0.52; 95% confidence interval (CI) = 0.49–0.55] and early re‐admittance risk (OR = 0.87; 95% CI = 0.85–0.92) compared to non‐obese patients. Malnourished patients had a much higher risk of death when in hospital (OR = 1.73; 95% CI = 1.62–1.85) or of being re‐admitted within 30 days after discharge (OR = 1.29; 95% CI = 1.22–1.38), even after adjusting for possible confounding factors. Conclusions: Obesity in patients hospitalised for COPD substantially reduces in‐hospital mortality risk and the possibility of early re‐admittance. Malnutrition is associated with an important increase in in‐hospital mortality and risk of re‐admittance in the 30 days following discharge.